Early Detection And Monitoring Of Hypertension Of Pregnant And Public Women With The Smartphone-Based Application "E-Demos" (Early Detection Of Hypertension Monitoring) In Soropia District - Hikmandayani, Hikmandayani; Kartini, Kartini; Farming, Farming; Nurhidayah, Nurhidayah; Agustini, Rahma Dewi (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2025)
Maternal Mortality Rate (MMR) reflects the risks faced by mothers during pregnancy and childbirth, which are influenced by the mother's nutritional status, socio-economic conditions, unfavorable conditions before pregnancy, the incidence of various complications during pregnancy and birth, the availability and use of health service facilities including perinatal services. and obstetrics. Monitoring pregnancy conditions is very important. High levels of maternal mortality caused by complications during pregnancy, childbirth and postpartum can be detected to prevent death and disability. According to the INAHS Consensus, in 2020. So there is a need for action to change through accelerating early detection of hypertension risk factors independently with digitalization.Early detection of hypertension is one of the screening tools designed for ordinary people, especially pregnant women and postpartum mothers in this digital era. Accelerating early detection with digitalization can be done by the public with the help of a simple Android-based application called e-Demos (Early Detection and Hypertension Monitoring). The aim of this research is to create a model for the development of health technology in the medical world using the Android Studio application on a smartphone, to determine the effectiveness of the "E-Demos" application instrumentation in detecting and monitoring hypertension in pregnant and postpartum women. This type of research is experimental research with an approach quasi-experimental (quasi-experiment) with non-equivalent control group design. This research uses methods and Android application development to obtain data digitally. Research and Development is a process or steps to develop a new product.